Music in the National Folklore Ensamble: notes and reflections on its beginning and its subsequent projection, on the 50th anniversary of its foundation - López Alcas, Ricardo (2023)
This text deals with the music and musicians who were part of the first group that joined the newly founded Conjunto Nacional de Folklore in the 1970s. To do so, it begins by describing the context in which its creation took place and how the process of appointing Victoria Santa Cruz as its director unfolded. Next, to address the music within the artistic entity, three aspects are presented: first, an account is given of the profile that the musicians were expected to have in the director's vision, how this played out in practice, as well as a register of the names of the first members. Then, the role of the musical advisor in the artistic group is described, before finally providing an overview of the music played in the first years of the ensemble, drawing on various documentary materials and some oral testimonies. As a complement to all of the above, and prior to some final reflections, it is also shown how a public institution today is symbolically trying to continue the group founded by Victoria Santa Cruz 50 years ago.